just a quick question, what am I doing wrong here? x = 5/2
(1/4)^(1-x) = 8
4^(-1+1-x) = 2^3
4^(-x) = 2^3
2^2(-x) = 2^3
2(-x) = 3
-x = 3/2
x = -3/2 ?
the line highlighted red is where you made the mistake. you should not have added the powers, you should have multiplied them. we add powers when we multiply two numbers having the same base. here we were raising a number to a power. we multiply the powers in this case
EDIT: Ok, Glaysher already answered your question. My apologies for butting in Glaysher